PO254 Reorganisation of stroke services in queen elizabeth central hospital (qech), blantyre malawi – establishing an international link. (1st December 2017) - Benjamin, Laura; Solomon, Tom; Browning, Simone; Phiri, Tamara; Mallewa, Jane; Gordon, Stephen; Edwards, Selina; Brown, Martin; Simister, Robert
Abstract : Background: Stroke incidence and mortality is increasing in low-to-middle income countries. This trend translates locally to Queen Elizabeth Central Hospital (QECH) Blantyre Malawi; where stroke is already the third highest cause of mortality and fifth most common presentation to the hospital. Aim: To develop an international partnership to improve stroke care, primarily by setting up a stroke unit; through this, we hope to improve clinical services, and develop a training and research platform. Findings: Potential areas for a UK-Malawi collaboration were identified. For example, providing access to protocols and training staff to support inpatient and outpatient services, rotating UK health professionals to disseminate skills, and to equip the stroke unit to support optimal care. Conclusions: This trip provided a forum to foster an international partnership, and an exciting opportunity to address the burden of stroke, in the context of improving clinical care, stroke research and training.